+0  
 
0
23
1
avatar

The solutions of x(x - 3) = 2 may be expressed in the form (a + sqrt(b))/c and (a - sqrt(b))/c, where a, b, and c are prime numbers. Find a + b + c.

 
 Jun 4, 2021

Best Answer 

 #1
avatar+32592 
+2

Expand to get

x^2 -3x -2 = 0         Use quadratic fromula        a = 1   b = -3   c = -2

 

\(x = {-(-3) \pm \sqrt{(-3^2)^2-4(1)(-2)} \over 2(1)}\)       to get your answer.............

 
 Jun 4, 2021
 #1
avatar+32592 
+2
Best Answer

Expand to get

x^2 -3x -2 = 0         Use quadratic fromula        a = 1   b = -3   c = -2

 

\(x = {-(-3) \pm \sqrt{(-3^2)^2-4(1)(-2)} \over 2(1)}\)       to get your answer.............

 
ElectricPavlov Jun 4, 2021

12 Online Users

avatar
avatar
avatar